The Comparative Proteomics of Ubiquitination in Mouse - Semple, Colin A.M.; RIKEN GER Group; GSL Members (Genome Research, 2003)
Ubiquitination is a common posttranslational modification in eukaryotic cells, influencing many fundamental cellular processes. Defects in ubiquitination and the processes it mediates are involved in many human disease states. The ubiquitination of a substrate involves four classes of enzymes:a ubiquitin-activating enzyme (E1), a ubiquitin-conjugating enzyme (E2), a ubiquitin protein ligase (E3), and a de-ubiquitinating enzyme (DUB). A substantial number of E1s (four), E2s (13), E3s (97), and DUBs (six) that were previously unknown in the mouse are included in the FANTOM2 Representative Transcript and Protein Set (RTPS). Many of the genes encoding these proteins will constitute promising candidates for involvement in disease. In addition, the RTPS provides the basis for the most comprehensive survey of ubiquitination-associated proteins across eukaryotes undertaken to date. Comparisons of these proteins across human and other organisms suggest that eukaryotic evolution has been associated with an increase in the number and diversity of E3s (possessing either zinc-finger RING, F-box, or HECT domains) and DUBs (containing the ubiquitin thiolesterase family 2 domain). These increases in numbers are too large to be accounted for by the presence of fragmentary proteins in the data sets examined. Much of this innovation appears to have been associated with the emergence of multicellular organisms, and subsequently of vertebrates, increasing the opportunity for complex regulation of ubiquitination-mediated cellular and developmental processes.
10.1101/gr.980303